Study of the Frequency and Outcome of Acute Respiratory Tract Infection in Exclusively Breastfed Infants - Ahmmad, Be-Nazir; Sarker, Sanchita; Hossain, Md Mosharrof; Islam, Md Rokibul; Parvin, Rukhsana; Hossain, Md Asgar (Medicine Today, 2023)
Introduction: Exclusive breast feeding is the fundamental component of child nutrition and survival. Exclusive breast feeding provides nutritional and immunological support for infant normal growth and development. Bangladesh is traditionally a breastfed community. The risks of acute respiratory infection (ARI) is higher in partially breastfed and formula-fed infants during the first 4 months of life. Objective: To see frequency and outcome of ARI in exclusively breastfed (EBF) infants. Materials and Methods: This cross sectional study was done at Department of Pediatrics, Rajshahi Medical College Hospital, from January 2013 to June 2013, a period of six months to find out the frequency and outcome of acute respiratory tract (ARI) infection in exclusively breastfed infants. 100 cases of infants suffering from ARI were selected who were exclusively breastfed. Data were analyzed through SPSS software. Results: Most of the EBF babies (M48+F28=) 76% came to hospital with a history of one or two attacks of ARI. Among 100 EBF babies, 96 babies were cured without complications and 02 babies develop complications and cured. There was 02 unfortunate death. Only 42% of EBF babies presented with moderate or less severe attack, 58% had mild attack. Hospital stays in EBF babies are shorter, only 64% of EBF patients had to stay more than 03 days. Conclusion: Frequency and severity of ARI attack is less and mild and hospital staying is short found in EBF babies, as well as better outcome with treatment. Medicine Today 2023 Vol.35(1): 16-19